The prevalence of Helminth parasites in the gastro-intestinal tract of wild African sharptooth catfish Clarias gariepinus (Siluriformes: Clariidae) in Gwagwalada, Nigeria - Dan-kishiya, Ahmed S. (2013)
A study on the gastro-intestinal helminth parasites of wild C. gariepinus was carried out in Gwagwalada Area Council of FCT, Abuja, Nigeria. A total of 110 samples were examined which includes 42 males and 68 females. Forty-eight (43,64%) fishes were infected with various species of helminth, which includes Wenyonia spp (28,18%), Procamallanus laevionchus (11,82%) and Euclinostomum heterostomum (3,64%). The female fish had the highest percentage prevalence (28,18%) while the males had 15,46% prevalence. Most of the parasites were recovered from the intestinal lumen. There was some degree of specificity in their distribution within the host but there was no significant difference (P>0,05) between the standard length, body weight, number of fish infected, prevalence and the intensity of infection.KEY WORDSHelminth parasites, Wild, C. gariepinus, Gastro-intestinal tract, Gwagwalada